Unveiling Polyindole: Freestanding As-electrospun Polyindole Nanofibers and Polyindole/Carbon Nanotubes Composites as Enhanced Electrodes for Flexible All-solid-state Supercapacitors. (1st September 2017) - Tebyetekerwa, Mike; Yang, Shengyuan; Peng, Shengjie; Xu, Zhen; Shao, Wenyu; Pan, Dan; Ramakrishna, Seeram; Zhu, Meifang
Graphical abstract: Polyindole and polyindole/Carbon nanotubes nanofibers were fabricated via electrospinning as flexible electrodes. They showed an improved capacitance of up to 238 F g−1 and 476 F g−1 at 1.0 A g−1 for Pind and Pind/CNT, respectively. Highlights: Polyindole nanofibers were fabricated and employed for the first time in supercapacitors. Remarkable specific capacitance of Polyindole nanofibers as high as 238 F g −1 (1.0 A g −1 ) is reported. A single-step supercapacitor assembly with a high energy density of 17.14 W h kg −1 at a power density of 426 W kg −1 is demonstrated. Abstract: Polyindole(Pind) is one of the conducting polymers (CPs) which previously was less studied but of recent is gaining attention for energy storage applications. In all the few previous reports, when Pind was employed as electrode active material in supercapacitors, the capacitance was reported low with reasonable values only being obtained as a composite with other materials. The reasons underlying the poor performance of Pind and Pind nanocomposites are thought to be: 1) inactive morphology and limited surface area, 2) poor conductivity, and 3) poor electrode fabrication techniques. To address the trio, we employed the traditional, easy and scalable electrospinning technique to fabricate high surface area electroactive Pind nanofibers. Further, a little percentage (10 wt.%) of carbon nanotubes (CNTs) were added to enhance the conductivity of Pind and to study the effect of our fabrication route on the nanocomposites. Significant capacitance improvements of up to 238 F g −1 and 476 F g −1 at 1.0 A g −1 for Pind and Pind/CNT freestanding electrospun electrodes, respectively were achieved. Moreover, we report the significant performance of the all-solid-state symmetric, flexible and binder-free supercapacitor fabricated by a one-step and scalable method of as-electrospun Pind/CNT nanofibers on the stainless steel fabric current collector. The supercapacitor showed a high energy density of 17.14 W h kg −1 at a power density of 426 W kg −1 and capacitance retention of 95% after 2000 cycles. We strongly believe that we have set a stage for Pind to compete in a healthy race with other CPs as a next generation electrode material for supercapacitors.